Rhodamine spiroamides for multicolor single-molecule switching fluorescent nanoscopy - Belov, Vladimir N. (2009)
The design, synthesis, and evaluation of new rhodamine spiroamides are described. These molecules have applications in optical nanoscopy based on random switching of the fluorescent single molecules. The new markers may be used in (co)localization studies of various objects and their (mutual) positions and shape can be determined with a precision of a few tens of nanometers. Multicolor staining, good photoactivation, a large number of emitted photons, and selective chemical binding with amino or thiol groups were achieved due to the presence of various functional groups on the rhodamine spiroamides. Rigidized sulfonated xanthene fragment fused with six-membered rings, N,N′-bis(2,2,2-trifluoroethyl) groups, and a combination of additional double bonds and sulfonic acid groups with simple aliphatic spiroamide residue provide multicolor properties and improve performance of the rhodamine spiroamides in photoactivation and bioconjugation reactions. Having both essential parts of the photoswitchable assembly - the switching and the fluorescent (reporter) groups - combined in one chemical entity make this approach attractive for further development. A series of rhodamine spiroamides is presented along with characterizations of their most relevant properties for application as fluorescent probes in single-molecule switching and localization microscopy. Optical images with resolutions on the nanometer scale illustrate the potential of the labels in the colocalization of biological objects and the two-photon activation technique with optical sectioning.